Novel Descriptor-Driven Design of Molten Alloys for Methane Pyrolysis - Han, Seung Ju; Seo, Jeong Cheol; Park, Gyungah; Son, Ju Ho; Lee, Yunjo; Kim, Seok Ki (ACS Catalysis, 2024)
Clean hydrogen production via methane pyrolysis using molten metal alloy catalysts is an interesting approach. However, the high temperatures and dynamic conditions required for pyrolysis render in situ observation of the molten metal system difficult. In this study, we identified two descriptors (H* formation energy and solute metal diffusivity) based on ab initio molecular dynamics simulations to predict the catalytic activity of Bi-based binary alloys (M = Ni, Pt, Cu, Ag) in methane pyrolysis. The solute metals were active sites for strong hydrogen adsorption, whereas solute metal diffusivity determined the extent of its exposure on the surface of the molten metal bubbles. Based on these findings, we identified two ternary alloys (Bi-Ni-Cu and Bi-Ni-Mn) that are catalytically more active than the binary Bi-Ni alloy. This study promotes the theory-based screening of highly active alloy catalysts for methane pyrolysis, thus contributing to the advancement of hydrogen society.
Keywords: Alloy catalyst; Bubble column reactors; Descriptors; High dynamic; High temperature condition; Metal alloys; Metal diffusivity; Methane pyrolysis; Molten alloy; Solute metals; bubble column reactor; computational chemistry; hydrogen production; methane pyrolysis; molten metal